Heels for her - Adus, Azrul Azizi; Adzhari, Mohd Saiful; Mahalan, Marita; Sukiaw, Andilika (2009)
1.2 INTRODUCTION Every business must have vision and mission to ensure that they can achieve their goal. Vision is long term goal and mission is short term goal. Then to set up a business the entrepreneur must decide a good vision and mission regarding their business.